2014
DOI: 10.1002/bit.25295
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic honeycomb‐like scaffold prepared by flow‐focusing technology for cartilage regeneration

Abstract: A tissue engineering chondrocytes/scaffold construct provides a promise to cartilage regeneration. The architecture of a scaffold such as interconnections, porosities, and pore sizes influences the fates of seeding cells including gene expression, survival, migration, proliferation, and differentiation thus may determine the success of this approach. Scaffolds of highly ordered and uniform structures are desirable to control cellular behaviors. In this study, a newly designed microfluidic device based on flow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The ability to incorporate biomolecules (such as enzymes) into the porous films produced by multi-step methods, such as breath figure (8), can be greatly limited, since organic solvents (such as dichloromethane and carbon disulfide) are involved in the preparation process (9), which often damage the biomolecules. On the other hand, the more simplified (one-step) methods, such as the conventional casting of films (3) produce porous films with non-controlled pore sizes (10). As a result, we believe that there is a pressing need for developing new methods for the preparation of porous structures with controlled porosity, without involving harsh conditions, such as the involvement of organic solvents, heat treatments, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to incorporate biomolecules (such as enzymes) into the porous films produced by multi-step methods, such as breath figure (8), can be greatly limited, since organic solvents (such as dichloromethane and carbon disulfide) are involved in the preparation process (9), which often damage the biomolecules. On the other hand, the more simplified (one-step) methods, such as the conventional casting of films (3) produce porous films with non-controlled pore sizes (10). As a result, we believe that there is a pressing need for developing new methods for the preparation of porous structures with controlled porosity, without involving harsh conditions, such as the involvement of organic solvents, heat treatments, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This bubble-based scaffold is fabricated using the flow-focusing method with a microfluidic device (Chung, Mishra, Wang, Lin, & Lin, 2009). Compared to those scaffolds prepared using the traditional freeze-dried method, the bubble-based scaffolds have a relatively higher swelling ratio, porosity, compressive strength, and expansion capacity (Wang et al, 2014(Wang et al, , 2016.…”
mentioning
confidence: 99%
“…The use of autologous MSCs to repair articular cartilage defects has been proposed . In fact, clinical approaches including Pridie's procedure, abrasion arthroplasty, and microfracture surgery all involve stimulating bone marrow to recruit MSCs from the subchondral bone for cartilage regeneration . Although still not used in daily practice, the use of intra‐articular injections of MSCs has been proposed to treat articular cartilage injuries caused by trauma and osteoarthritis (OA).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In fact, clinical approaches including Pridie's procedure, abrasion arthroplasty, and microfracture surgery all involve stimulating bone marrow to recruit MSCs from the subchondral bone for cartilage regeneration. 11,12 Although still not used in daily practice, the use of intra-articular injections of MSCs has been proposed to treat articular cartilage injuries caused by trauma and osteoarthritis (OA). Phase I/II trials are currently being conducted, and preliminary results at 6 months postoperation showed that MSCs injection into the osteoarthritic knee improved function and pain without causing adverse events, and reduced cartilage defects by regeneration of hyaline-like articular cartilage.…”
Section: Introductionmentioning
confidence: 99%